Community perceptions of universal health coverage in eight districts of the Northern and Volta regions of Ghana - Kalifa J. Wright; Adriana Biney; Mawuli Kushitor; John Koku Awoonor-Williams; Ayaga A. Bawah; James F. Phillips (Taylor & Francis Group, 2020)
Background: Ever since Ghana embraced the 1978 Alma-Ata Declaration, it has consigned priority to achieving 'Health for All.' The Community-based Health Planning and Services (CHPS) Initiative was established to close gaps in geographic access to services and health equity. CHPS is Ghana's flagship Universal Health Coverage (UHC) Initiative and will soon completely cover the country with community-located services. Objectives: This paper aims to identify community perceptions of gaps in CHPS maternal and child health services that detract from its UHC goals and to elicit advice on how the contribution of CHPS to UHC can be improved. Method: Three dimensions of access to CHPS care were investigated: geographic, social, and financial. Focus group data were collected in 40 sessions conducted in eight communities located in two districts each of the Northern and Volta Regions. Groups were comprised of 327 participants representing four types of potential clientele: mothers and fathers of children under 5, young men and young women ages 15-24. Results: Posting trained primary health-care nurses to community locations as a means of improving primary health-care access is emphatically supported by focus group participants, even in localities where CHPS is not yet functioning. Despite this consensus, comments on CHPS activities suggest that CHPS services are often compromised by cultural, financial, and familial constraints to women's health-seeking autonomy and by programmatic lapses constrain implementation of key components of care. Respondents seek improvements in the quality of care, community engagement activities, expansion of the range of services to include emergency referral services, and enhancement of clinical health insurance coverage to include preventive health services. Conclusion: Improving geographic and financial access to CHPS facilities is essential to UHC, but responding to community need for improved outreach, and service quality is equivalently critical to achieving this goal.